THE METHODOLOGY OF THE DEVELOPMENT OF COMPETENCY-BASED APPROACH IN PEDAGOGY - Chehlova, Zoja; Chehlovs, Mihails; Gode, Ina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the 21st century, under the conditions of the common European labour market and common information space, the issue concerning educating competent individuals able to work productively and communicate effectively in different life situations has become increasingly important. The competency-based approach has become a topical issue in pedagogy. The aim of the article is to analyse the development of the methodology of the competency-based approach in pedagogy and to consider the essence and the structure of the competency-based approach. Results: the concept was approbated in the educational process in Pushkin Lyceum in Riga; there were obtained positive results in the development of the educational competency of the Lyceum students.